Safe Sleep for Hospitalized Infants. Issue 1 (January 2016) - McMullen, Sherri L.; Fioravanti, Irene Dutko; Brown, Kristen; Carey, Mary G.
Abstract: Background: The American Academy of Pediatrics (AAP) published expanded safe sleep guidelines in 2011. Objective: The purpose of this quality improvement project was to promote the AAP safe sleep recommendations and provide appropriate role modeling of these recommendations for hemodynamically stable infants throughout their hospital stay. Design and Intervention: A safe sleep educational initiative for parents and hospital staff included an observation of infant sleep practice before and after the initiative and a pre- and posteducation questionnaire of nurses' knowledge, attitudes, and opinions. Setting and Participants: A Magnet-designated urban hospital that included 72 pediatric beds, a 60-bed NICU, and 41 mother–baby beds; and 658 pediatric and obstetric nurses. Results: One-hundred percent of nurses received the educational intervention. Observations noted an improvement from 70% to 90% ( p < 0.01) of infants in a safe sleep position when comparing pre- and postintervention results. There were some improvements in knowledge of and agreement with the AAP guidelines after the educational intervention, but not as much as expected. Conclusions: There was inconsistency between nursing knowledge and practice about safe infant sleep. Nurses were aware of the AAP recommendations, but it took time to achieve close to full compliance in changing clinical practice. Observation was an important part of this initiative to reinforce knowledge and role model best practice for parents. Abstract : A quality improvement project to promote safe sleep for hospitalized infants is reported. The project covered eight pediatric units, the neonatal intensive care unit, and the mother-baby unit. Success came slower than expected, however challenges in engaging nurses and other caregivers in the project were eventually overcome.